Transforming cinema on YouTube: An integrative review of aesthetics, commodification, and socio-economic shifts - Rozi, Romdhi Fatkhur; Kenneth Tze Wui, Lee; L Dyah Purwita, Wardani (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2025)
The rise of digital platforms has profoundly transformed film production and consumption, shifting cinema to internet-based media like YouTube. This development necessitates an understanding of how film aesthetics, viewing practices, and industrial structures evolve in the digital age. While prior scholarship mainly examined industrial transitions and social media’s influence, there’s a critical gap in how digital platforms, specifically YouTube, reconfigure cinematic aesthetics and ontology. This study employs a qualitative integrative literature review to examine how YouTube, as a platform, rearticulates cinema’s aesthetic dimensions and ontology. Key findings reveal three core themes: YouTube reimagines early cinematic aesthetics (e.g., short duration, spectacle) as “digital attraction” through algorithmic optimization; it operates as a modern exhibition machine, commodifying content via its interface and algorithms; and these platform-driven dynamics generate significant socio-economic implications, compelling cinematic labor into a “prosumer” model and transforming traditional film consumption into a “hyper-social non-place”. Ultimately, YouTube embodies a paradoxical hybrid cinematic environment, challenging filmmakers or content creators to balance artistic integrity with commercial demands. This study highlights the need to critically re-evaluate cinema’s evolving form and function.